Avaliação e intervenção fisioterapêutica em paciente com mielite transversa decorrente de infecção por vírus chikungunya: relato de caso - CONCEIÇÃO, Ana Beatriz Souza da (2022)
Objective Describe the proposed physical therapy management for a patient diagnosed with Transverse Myelitis due to Chikungunya virus infection. Methods We report the case of transverse myelitis due to Chikungunya virus infection in a 29-year-old patient, the assessment methods and the physical therapy intervention used to manage lower limb pain, mobility and strength. Pain intensity was assessed using the Visual Analog Scale (VAS). The superficial tactile sensitivity by the esthesiometer, the painful one by the sharp end of the reflex hammer and the thermal one with hot and cold test tubes. Functional mobility and lower limb strength were assessed using the Timed Up and Go and 30s Chair-Stand tests, respectively. The physical therapy protocol consisted of kinesiotherapy and electrothermophototherapy. Results At the end of the 20 sessions, a reduction in pain was observed in all joints tested by the VAS. There was an increase in the time to perform the TUG and in the number of repetitions during the 30CST, in addition to the patient being able to perform the tests with more autonomy and without the help of the companion. Conclusion After the assessment and physical therapy intervention, improvements in the aspects of pain, mobility and strength of the lower limbs were obtained, in addition to improvement in the symptoms of constipation and urinary incontinence. Impact This report presents a case of transverse myelitis resulting from Chikungunya virus infection with a delayed diagnosis and poor prognosis never reported in the literature. It provides physiotherapists with a detailed physiotherapy assessment and intervention protocol that can guide similar cases of neurological complications arising from arboviruses.